PEMETAAN STANDAR NASIONAL PENDIDIKAN PADA SEKOLAH DASAR DAN MADRASAH IBTIDAIYAH KOTA PAYAKUMBUH TAHUN 2013 - Adnan, Aryadie (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
This research is based on the condition of basic education (Elementary School and Islamic Vocational Elementary School), vision, mission of development, and Local Middle-term Development Planning (RPJMD) 2012-2017 Payakumbuh City. This quantitative research tries to compare the standard of basic education with National Education Standard. It uses sampling census technique which means all the populations became samples.There are 75 schools as the populations in Payakumbuh. The data have been collected by using questioners and have been analized by using percentage statistics analysis. The result is classified into 5 categories. It shows that the condition of basic education in Payakumbuh are in accordance with National Education Standard. There are not any schools which have very good catagories, there are 9 schools (14,3 %) which have good categories, there are 31 schools (49,2 %) which have fair categories, there are 19 schools (30,2 %) which have poor categories and there are 3 schools (4,8 %) which have very poor categories. In brief, the government must have the right policies and plannings towards the development of basic education in Payakumbuh in order to keep up with National Education Standard. Keywords: Vision dan mission, National Education Standards, educational policy